Manuel Vicente explained... turning South - Milheiro, A. V. (2021)
Manuel Vicente can be explained in many ways. He was born in Lisbon in 1934 and died there in 2013. He was a man with a huge European culture, tempered by visits to the America of Louis Kahn and Robert Venturi, giants with whom he was in close contact. He was always in transit to Macao, towards the East. A man who felt flabbergasted in Goa. A fierce Lisbonite. An artefact collector. A narrator of invented memories. A voyeur in the best architectural tradition. A teacher. A postmodern. From an early age, Manuel Vicente expressed his empathy for a world not completely made of lights, because it made itself available to unpredictability and a minimally regulated incongruity. For him, to be an architect "was really a life more than a profession," as he testified in a testimony in the 1980s.